Foucault on the Wards: Rediscovering Reflection as a Social Pediatrician in Training. (March 2020) - Maynard, Kevin
Abstract : The author states that as a second-year medical student with a liberal arts degree, it was often difficult for him to reconcile his former liberal arts education with the current demands of his training. Although the medical curriculum increasingly acknowledges the importance of a biopsychosocial model, the prioritization of knowledge remains the same: know your biological, pharmacological, and anatomical facts. However, the author's experience with a social pediatrics research summer studentship moved him beyond this basic sciences mindset and provided a practical framework for the application of his liberal arts training. The experience was twofold: he worked on a research project while simultaneously shadowing a pediatrician twice a week. His project applied a Foucauldian critical discourse analysis (CDA) to an archive of texts that sought to better characterize the term social pediatrics. The author concludes that the thought-changing reflection, mentorship, and concrete clinical experiences made possible by the summer studentship expanded his worldview. The author discusses the complementary relationship between CDA, clinical experience, and self-reflection in the developing clinician. The purpose of his essay is threefold. First, by drawing on concepts from Descartes' Meditations and Plato's allegory of the cave, he establishes educational continuity between his liberal arts and medical training. Second, using clinical examples, he explores the practicality of discourse analysis and how skills regarding empathy and bias awareness are transferrable to the wards. Last, he highlights the importance of cognitive dissonance and transformative learning in the maturing physician.